2012
DOI: 10.1002/emmm.201101094
|View full text |Cite
|
Sign up to set email alerts
|

Casein kinase I epsilon interacts with mitochondrial proteins for the growth and survival of human ovarian cancer cells

Abstract: Epithelial ovarian cancer is the leading cause of death among gynaecologic cancers in Western countries. Our studies have shown that casein kinase I‐epsilon (CKIε), a Wnt pathway protein, is significantly overexpressed in ovarian cancer tissues and is associated with poor survival. Ectopic expression of CKIε in normal human ovarian surface epithelial cells and inhibition of CKIε in ovarian cancer cells and in xenografts demonstrated the importance of CKIε in regulating cell proliferation and migration. Interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 47 publications
3
48
2
Order By: Relevance
“…Our results are consistent with the data of Lin and coworkers, who recently demonstrated that CK1ɛ expression in oral cancer is related to considerably better overall survival compared to patients with CK1ɛ negative tumors . Contrarily, Rodriguez and coworkers showed that overexpression of CK1ɛ in ovarian cancer is associated with poor survival, strengthening the hypothesis that the role of CK1ɛ in carcinogenesis varies in different cancer entities.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are consistent with the data of Lin and coworkers, who recently demonstrated that CK1ɛ expression in oral cancer is related to considerably better overall survival compared to patients with CK1ɛ negative tumors . Contrarily, Rodriguez and coworkers showed that overexpression of CK1ɛ in ovarian cancer is associated with poor survival, strengthening the hypothesis that the role of CK1ɛ in carcinogenesis varies in different cancer entities.…”
Section: Discussionsupporting
confidence: 92%
“…In some types of cancer, CK1α seems to exhibit oncogenic features by promoting proliferation, genome instability and inhibition of apoptotic processes, such as ovarian cancer, 26 acute myelocytic leukemia 27 and so on, which are supported by the fact that CK1α is often overexpressed in those tumors and correlates with poor survival. Although in some other types of cancer, such as colorectal carcinoma, lymphomas and breast carcinomas, 28 CK1α acts as a tumor suppressor which is evidenced by the fact that loss of heterozygosity of CK1α gene causes a highly invasive carcinoma and reduced CK1α expression was often observed in those tumors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, while previous literature identifies CSNK1e as a modulator of circadian rhythms (Preuss et al 2004) (Badura et al 2007) (Meng et al 2008), more recent studies do not confirm its essential role in this pathway (Sekine et al 2008) (Walton et al 2009). In contrast, CSNK1e has been implicated in cancer, both in ovarian (Rodriguez et al 2012) and in breast cancer, where its function is linked to the activity of the WNT pathway (Kim et al). CSNK1e has also been shown to be required for transcriptional response to hedgehog (HH) signaling (Varjosalo et al 2008) and in this respect, it is worthwhile to point out that GLI1, the main transcriptional mediator of HH signaling, also emerged as MYC-SL gene.…”
Section: Myc Synthetic Lethal Genes and The Hallmarks Of Mycmentioning
confidence: 99%